Driving towards the future: Investigating senior tourist acceptance factors of autonomous vehicles in travel and tourism - Qingyu, Zhang; Khan, Salman; Mehmood, Shafaqat; Khan, Safeer Ullah (Journal of Tourism Management Research, 2024)
This paper investigates the role of autonomous vehicles in transforming mobility and tourism. By extending the understanding of self-driving cars within a tourism context, this paper enhances the Automation Acceptance Model and tests the effects of underexplored variables in tourism studies, such as social influence, prior knowledge, and openness to change as a moderator. Data were collected through a survey method, and responses from 269 participants were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). These results suggest that while the extension of the theoretical model is informative, the insignificance of six of the proposed hypotheses calls for deeper investigation in other contexts concerning user acceptance behaviors. This opens new directions for further research, particularly with regard to age, perceived safety, and the level of trust in the technology. The paper concludes with practical implications to help increase the acceptance of autonomous vehicles among senior tourists, discusses limitations, and provides recommendations for future investigation in this rapidly evolving area.